Роль армян в персидской армии в первой половине XIX века - Сергей Минасян (ՀՀ ԳԱԱ հրատ.)
Հայ-պարսկական հարաբերությունների պատմությունը ուսումնասիրողները արժանի ուշադրություն չեն դարձրել Պարսկական բանակում հայերի ունեցած դերին և երկու երկրների ռազմական համագործակցության պատմությանը։ Պատմական աղբյուրներում բազում վկայություններ կան այն մասին, որ հայերր մուսուլմանական Պարսկաստանում, ի տարբերություն նույն մուսուլմանական Թուրքիայի, իրավունք ունեին ոչ միայն զենք կրել, այլև պարսկական բանակում կազմել առանձին զորամասեր։ In the history of Persian-Armenian relations, the heroic role of the Armenians in the Persian army has not been given due consideration and interrelations of both countries in their common history have not yet been thoroughly studied. Historical sources indicate that Armenians have long been actively involved in the Persian army and have rendered commendable services, specifically at the beginning of the 19th century when Persia was at war with Russia.
Keywords: History; Military Science; D History